Measuring Quality of Public Participation in the Local Government of Bangladesh - Makhdum, Niaz; Rumi, Maruf Hasan; Islam, Naznin (Journal of Public Administration and Governance, 2023)
Public participation in local government is considered very crucial for ensuring good governance and quality service at the local level. This study aims to measure the level of public participation in the local government of Bangladesh. For this purpose, Arnstein’s citizen participation theory is used in this study. A cross-sectional quantitative approach has been followed in this study. To fulfill the research objectives, 400 samples were collected using the survey method from two divisions of Bangladesh, namely Dhaka and Rangpur. A semi-structured questionnaire was used in this study for conducting the survey. Major findings of this study revealed that existing mechanisms for citizens’ participation in the local government of Bangladesh are merely for eye-washing rather than for ensuring actual citizen participation. People cannot influence local government decisions through these existing mechanisms. In terms of Arnstein’s citizen’s participation theory, the level of public participation in the local government of Bangladesh is at the therapy level. It indicates that the existing mechanisms are only for making people cured by showing that the people have the opportunity to participate rather than using these mechanisms for ensuring actual citizens’ participation. However, the government and other respective authorities need to take necessary measures to ensure public participation in the local government of Bangladesh.